If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = -2n Solving -6 = -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. -6 + 2n = -2n + 2n Combine like terms: -2n + 2n = 0 -6 + 2n = 0 Add '6' to each side of the equation. -6 + 6 + 2n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2n = 0 + 6 2n = 0 + 6 Combine like terms: 0 + 6 = 6 2n = 6 Divide each side by '2'. n = 3 Simplifying n = 3
| 5(3-2x)-3(4-2x)=19 | | 7x+4+2x=-1 | | -8.1=y+7.8 | | 5x+9y=96 | | 5(x+2)-4(x-1)=6 | | 4(7y+2)=3(9y-2) | | 3x+4=10x-3 | | 4(x+3)-2x=7 | | 1+m+3m=-19 | | x^2-3x-12=20 | | 4(x-3)-2(x-1)=-6 | | -8x+3x+7=47 | | 2(x+2)=2(3x-2) | | 3-2x=-15 | | 9x+3y=-8 | | 32=-4m+8 | | 40X^2+131X+105=0 | | 15x-6=8x+4 | | 3y-6=-18 | | 3+4X=4-5 | | -15x-10=-10x | | 7-2x=-14 | | y+34=5 | | 3x^2=x+24 | | 7y-5=y-1 | | y+30=5 | | y+3-2=5 | | 4x+6.4=2(3x-2.4) | | 6+3*x=4-5 | | -3(5+1)-6=-9 | | -x-16=5(4x+1) | | -5n+12=-4n-19-12 |